PARADIGMATIC APPROACHES IN DIGNITY, CONSUMER, AND CLIENT STUDIES: A SYSTEMATIC REVIEW (REMUNOM, 2026)
The objective of this study is to present a systematic review of the literature on the paradigmatic approaches that deal with dignity, consumer, and client. It uses key elements to inform systematic reviews and meta-analyses (PRISMA) through a search based on the terms “dignity”, “customer” and “client”. The aim of this work is to analyze the publications that relate the aforementioned constructs, mainly in relation to their research paradigms, to understand which are the most used and if the paradigmatic approaches are the most appropriate for studying the theme. The work adds to the field by carrying out the first systematic literature review on the chosen topics, allowing new studies to be carried out based on the analyzes and findings and limitations. The work proposes that the structuralist paradigm based on Anthony Giddens be adopted for research related to dignity, clients/consumers, considering that the works that used it were the ones that produced the most innovative results for the field.Incluir o resumo em inglês.